Fatal conceit : [large type] a novel - Tanenbaum, Robert (Tanenbaum, Robert. Butch Karp and Marlene Ciampi series., 2014)
When the CIA director is murdered, Butch Karp finds himself battling a heavyweight opponent. The presidential election campaign's foreign policy mantra has been that the terrorists are on the run and Bin Laden is dead. It's rumored that the CIA chief was going to deviate from their version of events and that the administration may have been involved with this death. Can Karp expose the cover-up and find his missing daughter, who has been taken hostage by terrorists?